Dramma Giocoso : four contemporary perspectives on the Mozart/Da Ponte operas - Rushton, Julian (Collected writings of the Orpheus Institute, 2012)
In exploring the evergreen qualities of Don Giovanni and Le Nozze di Figaro, this collection of studies does not shun approaches that have foundations in established theory, but refracts them through such problems as the tension between operatic tradition and psychological realism, the co-existence of multiple yet equal plots, and the antagonism between the tenets of tradition and the need for self-actualization. In exploring such themes, the authors not only illuminate new aspects of Mozart's operatic compositions, but also probe the nature of musical analysis itself.